Relationship Between Circulating MicroRNAs and Left Ventricular Hypertrophy in Hypertensive Patients - Lopes, Elisangela C. P.; Paim, Layde R.; Carvalho-Romano, Luís F. R. S.; Marques, Edmilson R.; Minin, Eduarda O. Z.; Vegian, Camila F. L.; Pio-Magalhães, José A.; Velloso, Lício A.; Coelho-Filho, Otavio R.; Sposito, Andrei C.; Matos-Souza, José R.; Nadruz, Wilson; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Left ventricular hypertrophy (LVH) is a common complication of hypertension and microRNAs (miRNAs) are considered to play an important role in cardiac hypertrophy development. This study evaluated the relationship between circulating miRNAs and LVH in hypertensive patients. Methods: Two cohorts [exploratory (n=42) and validation (n=297)] of hypertensive patients were evaluated by clinical, laboratory and echocardiography analysis. The serum expression of 754 miRNAs in the exploratory cohort and 6 miRNAs in the validation cohort was evaluated by the TaqMan OpenArray® system and quantitative polymerase chain reaction, respectively. Results: Among the 754 analyzed miRNAs, ten miRNAs (miR-30a-5p, miR-let7c, miR-92a, miR-451, miR-145-5p, miR-185, miR-338, miR-296, miR-375 and miR-10) had differential expression between individuals with and without LVH in the exploratory cohort. Results of multivariable regression analysis adjusted for confounding variables showed that three miRNAs (miR-145-5p, miR-451 and miR-let7c) were independently associated with LVH and left ventricular mass index in the validation cohort. Functional enrichment analysis demonstrated that these three miRNAs can regulate various genes and pathways related to cardiac remodeling. Furthermore, in vitro experiments using cardiac myocytes demonstrated that miR-145-5p mimic transfection up-regulated the expression of brain and atrial natriuretic peptide genes, which are markers of cardiac hypertrophy, while anti-miR-145-5p transfection abrogated the expression of these genes in response to norepinephrine stimulus. CONCLUSIONS: Our data demonstrated that circulating levels of several miRNAs, in particular miR-145-5p, miR-451 and let7c, were associated with LVH in hypertensive patients, indicating that these miRNAS may be potential circulating biomarkers or involved in hypertension-induced LV remodeling.